Juvenile primary fibromyalgia syndrome: A Review- Treatment and Prognosis - Maya Levy Coles; Yosef Uziel (BMC, 2021)
Abstract Juvenile primary fibromyalgia syndrome (JPFS) is a chronic musculoskeletal pain syndrome affecting children and adolescents. In part one of this review, we discussed the epidemiology, etiology, pathogenesis, clinical manifestations and diagnosis of JPFS. Part two focuses on the treatment and prognosis of JPFS. Early intervention is important. The standard of care is multidisciplinary, combining various modalities-most importantly, exercise and cognitive behavioral therapy. Prognosis varies and symptoms may persist into adulthood.